Lao People's Democratic Republic - Operational Costs of Trade-Related Sanitary and Phytosanitary Activities - World Bank (World Bank, 2012)
Information derived from sanitary and phytosanitary (SPS) surveillance and monitoring activities is an increasingly important requirement for market access and a crucial input for risk management and policymaking. This study report was undertaken with resources provided by the trade development facility multi donor trust fund to assist the Government of the Lao People's Democratic Republic (PDR) in assessing minimum levels of public operational funding needed to expand surveillance and diagnostic activities related to the management of SPS risks in Lao PDR. It provides policy options and recommendations for expanding the scope of current SPS activities, and assessments of additional operational costs needed for sustainably performing the recommended expanded activities. This introductory chapter describes SPS activities in general and the growth of SPS capacities in Lao PDR. Chapter two describes the scope and methodology of the study. Chapter three presents a basic discussion of issues and broad estimates of costs of laboratories and testing. Chapters four-six discuss present activities undertaken in the areas of food safety, plant health, and animal health, respectively, together with recommendations for their expansion and corresponding cost estimates. Chapter seven presents a summary of recommendations and conclusions.